Driver behavior and accident frequency in school zones: Assessing the impact of sign saturation. (September 2015) - Strawderman, Lesley; Rahman, Md Mahmudur; Huang, Yunchen; Nandi, Apurba
Highlights: Introduced the term sign saturation and presented a measurement method. The effect of sign saturation on school zone speed compliance was confirmed. Discovered a significant effect of sign saturation on number of accidents in school zones. The association of traffic density with vehicle speed, compliance, and accident rate was observed. Abstract: Based on the models of human information processing, if a driver observes too many of the same signs, he or she may no longer pay attention to those signs. In the case of school zones, this expected effect may lead to non-compliance to posted speeds, negatively impacting safety around nearby schools. This study aims to investigate the effect of the number of nearby school zones on driver behavior (vehicle speed and compliance) and accident frequency. As a measure of the density of school zones, this study introduced and defined a new term sign saturation and presented a methodology to calculate sign saturation for school zones. Results found a significant effect of sign saturation on vehicle speed, compliance, and accident frequency. This study also examined the speeding behavior in school zones for different time of the day and day of the week. Results found that speeding was more prevalent in the early mornings and during the weekends.